2012
DOI: 10.1038/eye.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pattern of ocular toxoplasmosis treated in a referral centre in Serbia

Abstract: Purpose To analyze the clinical pattern of ocular toxoplasmosis (OT) in a referral centre in Serbia.Patients and methods The medical records of consecutive patients admitted for OT to the single referral centre for uveitis in Serbia between 2006 and 2010 were retrospectively analyzed. OT was diagnosed on the basis of typical fundus lesions and positive serology for Toxoplasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…As shown in our study, out of a total of 80 eyes with ocular toxoplasmosis with SD-OCT examinations, 6 eyes were present with CME. Although with the application of SD-OCT, more eyes with CME probably could have been detected, our study had shown that CME is still rather uncommon [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As shown in our study, out of a total of 80 eyes with ocular toxoplasmosis with SD-OCT examinations, 6 eyes were present with CME. Although with the application of SD-OCT, more eyes with CME probably could have been detected, our study had shown that CME is still rather uncommon [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 57%
“…FA has been the traditional gold standard for the detection of CME in the past years; however, with the advent of OCT, more CME could be possibly observed with better reproducibility [8], [13]. Although CME in ocular toxoplasmosis was reported in previous publications, none of them evaluated CME with SD-OCT [14], [15], [16]. Thus, in the current study, we tried to use SD-OCT to maximize the detection of CME.…”
Section: Discussionmentioning
confidence: 98%
“…Toxoplasmosis is the most common cause of infectious posterior uveitis worldwide leading to severe vision loss, [1][2][3][4] although there is some evidence of decline in its prevalence in certain areas. [5] Ocular toxoplasmosis (OT) refers to eye disease related to infection from the obligate intracellular parasite Toxoplasma gondii.…”
Section: Introductionmentioning
confidence: 99%
“…Cells in the anterior chamber may also be noted and may appear to be either a granulomatous or non granulomatous uveitis. The discovery of healed pigmented retinochoroidal scars facilitates the diagnosis [57,58]. OT is also confirmed by a favorable clinical response to specific therapy.…”
Section: Diagnosis Is Based On Clinical Signs and Some Selected Biolomentioning
confidence: 79%